The relationship of psoriasis and melanocytic nevi - Fatma Pelin Cengiz; Nazan Emiroglu; Anil Gulsel Bahali; Dilek Biyik Ozkaya; Ozlem Su; Nahide Onsun (Wolters Kluwer Medknow Publications, 2016)
Background: There is limited data about the relationship between psoriasis and melanocytic lesions and melanoma. Immunologic pathways which were implicated in psoriasis induce a reduction in the number of melanocytic nevi. Aims and Objectives: To investigate the number of melanocytic nevi in psoriatic patients compared with controls and its relationship with disease severity and type of treatment. Methods: We performed a prospective study in 100 psoriatic patients and 100 controls. Clinical data were recorded for all participants. Results: As compared with controls, patients had overall fewer nevi congenital nevi. Among psoriatic patients, biologic agents and disease severity did not correlate with the number of nevi. Conclusions: Psoriatic patients have fewer nevi than controls. Frequency of nevi in psoriatic patients is not related to treatment and disease severity.